2015
DOI: 10.1161/atvbaha.115.305447
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Receptor Agonist Exenatide Increases Capillary Perfusion Independent of Nitric Oxide in Healthy Overweight Men

Abstract: Objective-The insulinotropic gut-derived hormone glucagon-like peptide-1 (GLP-1) increases capillary perfusion via a nitric oxide-dependent mechanism in rodents. This improves skeletal muscle glucose use and cardiac function. In humans, the effect of clinically used GLP-1 receptor agonists (GLP-1RAs) on capillary density is unknown. We aimed to assess the effects of the GLP-1RA exenatide on capillary density as well as the involvement of nitric oxide in humans. Approach and Results-We included 10 healthy overw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
0
29
2
Order By: Relevance
“…15 We recently demonstrated that exenatide increased skin capillary perfusion in healthy men, using the same techniques and a similar study protocol as used in the current study. 16 It was therefore unexpected to find no effect of exenatide on skin capillary perfusion in patients with type 2 diabetes mellitus in the current study. Such a differential effect in microvascular activity is also known for insulin, which improves microvascular perfusion in healthy volunteers, but has no effect on microvascular function in patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…15 We recently demonstrated that exenatide increased skin capillary perfusion in healthy men, using the same techniques and a similar study protocol as used in the current study. 16 It was therefore unexpected to find no effect of exenatide on skin capillary perfusion in patients with type 2 diabetes mellitus in the current study. Such a differential effect in microvascular activity is also known for insulin, which improves microvascular perfusion in healthy volunteers, but has no effect on microvascular function in patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 51%
“…For example, we recently demonstrated that exenatide infusion decreased neurogenic activity in healthy overweight men. 16 In that study, the effect on neurogenic activity was negatively correlated with capillary density, leading us to speculate that an exenatide-induced reduction in dermal SNS activity reduces vascular tone and consequently increases capillary density.…”
Section: Discussionmentioning
confidence: 83%
“…If GLP-1 RAs increase coronary blood flow, especially in patients with existing heart disease, this effect could reduce ischemia, infarct size, and risk of arrhythmias. A recent study in subjects with normal glucose tolerance demonstrated that GLP-1 infusion augments blood flow in small vessels in skeletal muscle and heart (35), and increased blood flow in small coronary vessels after myocardial ischemia has been shown to predict increased survival and reduced infarct size after MI (36). …”
Section: Potential Mechanisms To Explain CV Benefitmentioning
confidence: 99%
“…Interestingly, we observed a non‐significant decrease in TPR when exenatide was co‐infused with L‐NMMA. Although exenatide may induce NO‐independent vasodilation , it is unclear why this only occurred during L‐NMMA infusion in our study, and not also during exenatide infusion alone. Potentially, the vasodilator effects of exenatide can only be seen during a state of vasoconstriction in healthy subjects, as achieved by L‐NMMA infusion.…”
Section: Discussionmentioning
confidence: 92%